TINDAKAN KEKERASAN SEKSUAL DARI BERBAGAI KALANGAN YANG DITINJAU DALAM SUDUT PANDANG HUKUM ISLAM - Syam, Syafruddin (Hukum tata Negara/Siyasah, 2022)
This research was made to analyze the Factors of Acts of Sexual Violence from Various Groups Viewed from the Perspective of Islamic Law. as We see this from the point of view of Islamic law which is guided by the Alquran, regarding how the causes of sexual violence should have been contained in the law in the Alquran. Based on the research concluded in Islamic law which is guided by the Alquran, acts of sexual violence have been regulated long before the positive law came into force, as seen from Q.S An-Nur; 30-31, Q.S Al-Furqan; 43, and Q.S Al-Ahzab; 59 The Qur'an has previously warned about acts of sexual violence, by taking care of each other between men and women. Islam does not blame the victim as well as the perpetrator, the rules that have been set by Allah SWT. should be carried out and take care of each other.